2021
DOI: 10.3390/polym13111836
|View full text |Cite
|
Sign up to set email alerts
|

Development of Peptide-Based Nanoparticles for Mitochondrial Plasmid DNA Delivery

Abstract: A mitochondrion is a cellular organelle able to produce cellular energy in the form of adenosine triphosphate (ATP). As in the nucleus, mitochondria contain their own genome: the mitochondrial DNA (mtDNA). This genome is particularly susceptible to mutations that are at the basis of a multitude of disorders, especially those affecting the heart, the central nervous system and muscles. Conventional clinical practice applied to mitochondrial diseases is very limited and ineffective; a clear need for innovative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 55 publications
0
28
1
Order By: Relevance
“…The peptides used in this work were synthesized according to the protocol described in a previous work [18]. The synthesis of the PEI-DQA polymer was carried out in two steps: The first step was the synthesis of PEI-SA.…”
Section: Synthesis Of Peptides and Pei-dqamentioning
confidence: 99%
See 2 more Smart Citations
“…The peptides used in this work were synthesized according to the protocol described in a previous work [18]. The synthesis of the PEI-DQA polymer was carried out in two steps: The first step was the synthesis of PEI-SA.…”
Section: Synthesis Of Peptides and Pei-dqamentioning
confidence: 99%
“…2.2.3. Formulation of Peptide/pDNA and PEI-DQA/TAT/pDNA Complexes Peptide-based complexes were formulated according to the procedure described in a recent publication by our team [18]. PEI-DQA, TAT, and plasmid DNA stock solutions were prepared in sodium acetate buffer (0.1 mM sodium acetate/0.1 M acetic acid, pH 4.5) at a concentration of 0.5 mg/mL for PEI-DQA and TAT solutions, and 100 µg/mL for pDNA solutions.…”
Section: Nuclear Magnetic Resonance Spectroscopy (Nmr)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a library of fusion peptides with mitochondria targeting (mtCPP1) and cellpenetrating properties (Pepfect14, a stearylated CPP forming ASO nanocomplexes with splice-correction activity in cells [241]) that self-assembled with antisense oligonucleotides (ASO) into complexes was successful in knocking down mitochondrial mRNA [242]. A combinatorial approach to develop mitochondrial gene expression was also pursued by incorporating an MTS into WRAP peptides (short tryptophan/arginine rich peptides; [243]) which formed nanocomplexes with plasmid DNA encoding the mitochondrial ND1 gene that were taken up by cells and targeted to mitochondria [244]. Systematic analysis of CPPs and MTSs revealed that while both types of peptides were rich in Ala and Arg, the latter included Leu, suggesting a role for Leu in targeting to mitochondria [245].…”
Section: Mitochondrial Deliverymentioning
confidence: 99%
“…However, the transfection efficiency of eukaryotic cells with naked nucleic acids, such as plasmid DNA, is disfavored by the negative repulsion of cell membrane. In this field, several biomaterials based on cationic liposomes [9,10], peptides [11,12] and polymers [13,14] have been shown to be able to efficiently condense, protect, carry, and deliver nucleic acids to eukaryotic cells. For instance, chitosan and chitosan derivatives have been used as DNA delivery systems due to their cationic charge, biocompatibility, biodegradability, mucoadhesiveness and permeability-enhancing properties [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%